Uncovering Fraudulent Financial Reporting: Fraud Hexagon and the Moderating Role of Information Technology Adoption (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2025)
This research aims to examine the effect of the Fraud Hexagon dimensions on fraudulent financial reporting (FFR) in the banking sector in Indonesia, as well as analyze the moderating role of information technology (IT) adoption. Using a quantitative approach, this research using secondary data with purposive sampling technique to select 43 banks listed on the Indonesia Stock Exchange during the period 2020 to 2023. Financial reporting fraud is measured using the F-Score model, and the analysis technique used is PLS-SEM with WarpPLS 7.0 tools. The results showed that the opportunity (Ineffective Monitoring), and capability (CEO Change) had a positive effect in increasing the possibility of fraudulent financial reporting. Furthermore, IT adoption does not moderate the relationship between any of the Fraud Hexagon elements and FFR. These findings make an important contribution to the development of understanding of fraudulent financial reporting through fraud hexagon framework and technological approaches. The results of this research provide insights for banking regulators, auditors, and corporate policy makers in designing more effective fraud detection and prevention strategies.